THE TRIANGULAR LOVE OF MAIN CHARACTERS IN E. L. JAMES’ FIFTY SHADES DARKER (2011) - Hadianti, Karina Rahma (LANTERN (Journal on English Language, Culture and Literature), 2017)
This thesis focuses on love aspects shown in Fifty Shades Darker (2011) novel by E.L. James. Fifty Shades Darker novel describes the love relationship between the characters named Christian Grey and Anastasia Steele. The aim of this thesis is to prove the existence of love aspects in the novel by analyzing the intrinsic and extrinsic aspects. The writer uses library research to collect the data with the novel as the main data and several relevant books, journals, articles, also online documents and websites are used as the supporting data. The intrinsic aspects cover characters, setting, and conflicts. Meanwhile, in the extrinsic aspects, the writer elaborates Robert Sternberg’s triangular theory of love. Based on Robert Sternberg’s triangular theory of love, there are three components of love: intimacy, passion, and commitment. The result of this thesis proves that, according to Robert Sternberg’s triangular theory of love, both characters in the novel, Christian Grey and Anastasia Steele, have experienced intimacy, passion, and commitment in their love relationship.